MORPHOLOGICAL CHARACTER OF ONION (Allium ascalonicum L.) INDUCTION OF COLCHICINE MUTATION: KARAKTER MORFOLOGI BAWANG MERAH (Allium ascalonicum L.) INDUKSI MUTASI KOLKISIN - Wismaroh Saragih, Sanniwati (UPMI Proceeding Series, 2023)
This study aims to examine the morphological characteristics of shallots (Allium ascalonicum L.) using colchicine at various concentrations and soaking times. The results showed that the concentration of colchicine at 250 ppm was able to affect the morphology of shallot plants in terms of plant height, tuber diameter, and tuber fresh weight but had no effect on the number of leaves or tuber dry weight. A soaking time of 6 hours was able to affect the morphology of shallot plants on the rate of plant height and tuber diameter but did not affect the rate of the number of leaves, tuber fresh weight, or tuber dry weight. The interaction between colchicine concentration and soaking time showed that it was able to affect the performance of shallot plants in all observational variables except the dry weight of shallot bulbs. The concentration of colchicine and the time of administration are very influential in the induction of polyploid mutations. The studies summarized here can be a reference for the best soaking and concentration in combination with treatments that support the growth and production of local shallots in particular and varieties of shallots in general.